Are high flow nasal cannulae noisier than bubble CPAP for preterm infants? - Roberts, C T; Dawson, J A; Alquoka, E; Carew, P J; Donath, S M; Davis, P G; Manley, B J (Archives of disease in childhood. Fetal and neonatal edition, 2014)
Background Noise exposure in the neonatal intensive care unit is believed to be a risk factor for hearing loss in preterm neonates. Continuous positive airway pressure (CPAP) devices exceed recommended noise levels. High flow nasal cannulae (HFNC) are an increasingly popular alternative to CPAP for treating preterm infants, but there are no in vivo studies assessing noise production by HFNC. Objective To study whether HFNC are noisier than bubble CPAP (BCPAP) for preterm infants. Methods An observational study of preterm infants receiving HFNC or BCPAP. Noise levels within the external auditory meatus (EAM) were measured using a microphone probe tube connected to a calibrated digital dosimeter. Noise was measured across a range of frequencies and reported as decibels A-weighted (dBA). Results A total of 21 HFNC and 13 BCPAP noise measurements were performed in 21 infants. HFNC gas flows were 2–5 L/min, and BCPAP gas flows were 6–10 L/min with set pressures of 5–7 cm of water. There was no evidence of a difference in average noise levels measured at the EAM: mean difference (95% CI) of −1.6 (−4.0 to 0.9) dBA for HFNC compared to BCPAP. At low frequency (500 Hz), HFNC was mean (95% CI) 3.0 (0.3 to 5.7) dBA quieter than BCPAP. Noise increased with increasing BCPAP gas flow (p=0.007), but not with increasing set pressure. There was a trend to noise increasing with increasing HFNC gas flows. Conclusions At the gas flows studied, HFNC are not noisier than BCPAP for preterm infants.